Investigation of Periodic Modes in Nonlinear Systems with Fractional Order Integrator - Kavuran, Gurkan; Yeroglu, Celaleddin (Ieee, 2015)
This paper investigates the effect of fractional order integrator on the nonlinear feedback systems. The effect of fractional order integrator, which is proposed to place in front of relay with dead zone on the second order system, is analysed comparatively using Describing Function method and simulation results. Since the proposed approach provides the opportunity for the selection of a wide phase range, it can be considered as an effective method to select relevant sampling frequency and to investigate limit cycles in modulators and demodulators that are used for signal conversion applications.
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: Describing function; limit cycles; fractional order integrator; sigma-delta modulation